Kengo Kuma : Museo del canale Kitakami (1999) - Kuma, Kengo (2001)
Museo que responde a la topografía del terreno mimetizándose.
Keywords: JAPON; ISHINOMAKI; MIYAGI; MUSEOS; CONSTRUCCION SEMIENTERRADA